The value of diffusion weighted imaging in predicting the clinical progression of perforator artery cerebral infarction - Wenjing Yu; Jiajia Yang; Lulu Liu; Wenwen Song; Zhengxiang Zhang; Maosheng Xu; Zhijian Cao (NeuroImage: Clinical, 2022)
Objectives: To investigate the value of diffusion weighted imaging (DWI) in predicting the clinical progression of perforator artery cerebral infarction. Methods: The magnetic resonance imaging (MRI) data of patients with perforator artery cerebral infarction hospitalized in our hospital from October 2015 to February 2022 were analyzed retrospectively. Then we compared the differences of apparent diffusion coefficient (ADC) value, maximal size, location of cerebral infarction, clinical data and treatment plan between the two groups. Results: A total of 81 patients with perforating artery cerebral infarction were included, with 33 patients in the progressive cerebral infarction (PCI) group and 48 patients in the non-progressive cerebral infarction (NPCI) group. The ADC value in the progressive group was lower than that in the non-progressive group (P < 0.001), and ADC value was an independent factor influencing the clinical progression (OR = 0.974, 95 %CI = 0.960–0.989, P = 0.001); The average area of cerebral infarction in the progressive group was larger than that in the non-progressive group (P = 0.004). There was no difference between the two groups (P > 0.05) in terms of clinical data and treatment plan. Conclusions: The ADC value and maximal size of infarction were correlated with the clinical Progression. ADC value was an independent factor influencing the clinical progression of perforating artery cerebral infarction, which could be used for the prediction of clinical progress and provide guidance for the development of individualized treatment.